The Main Effects of Digital Marketers’ Work Behaviors on Sustainable Sweeping Innovations: The Moderating Role of Marketing Knowledge Within Telecommunication Companies - Jaffar, Zaid Abdulzahra; Omrane, Amina; Fleih, Ali Saheb (Journal of Ecohumanism, 2025)
The present study aims to determine the extent to which digital marketing business (i.e. digital attraction, digital communication, digital learning) helps achieving sweeping sustainable innovation (i.e. sustainable sweeping activities, sweeping sustainable exploitation, sweeping sustainable exploration), through the interactive role of marketing knowledge (i.e. knowledge of the market, knowledge of competitors, knowledge of customers, knowledge of technology). To test the interplay between those relevant variables, a quantitative research method was adopted; a total number of 400 questionnaires were distributed to a cross-section of EarthLink's clientele; and 384 of them were ultimately chosen. Statistical techniques and softwares (i.e. SPSS, Ver. 26. AMOS) were used to analyze the data and test the proposed hypotheses. Numerous suggestions were made in the study's final section.